Impact of the adjuvant management and risk factors on survival in FIGO stage 3 endometrial cancer patients - Tong, Nora; Kumar, Aalok; Gelowitz, Gerald; Tinker, Anna; Holloway, Caroline; Ko, Jenny (Frontiers in Oncology, 2023)
Objective: Patients with FIGO stage III endometrial cancer routinely receive adjuvant therapy. The purpose of this study was to evaluate overall survival (OS) and disease-free survival (DFS) in patients with stage IIIA to IIIC2 patients by treatment modality received and risk factors. Materials/methods: Patients with stage III endometrial cancer treated from 2000-2010 were identified in the provincial cancer registry. Clinicopathologic characteristics, adjuvant treatments and outcomes were compared using descriptive and multivariable analyses. Results: 261 patients had stage 3 endometrial cancer, 132 with stage IIIA, 9 with IIIB, 85 with IIIC1 and 35 with IIIC2. 39 had FIGO grade 1 disease; 73, grade 2; 147, grade 3. 160 had endometrioid and 35 had serous carcinoma. 161 patients received sequential adjuvant chemotherapy (CT) and radiotherapy (RT); 33 received RT only; 32 received CT only; 35 received neither. 5-year (5Y) DFS and OS were similar among stage IIIA (DFS 46.7%, OS 58.5%), IIIB (DFS 50.8%, OS 58.5%), IIIC1 (DFS 44%, OS 49.9%) and IIIC2 (DFS 42%, OS 41.6%). Use of adjuvant RT was associated with improved median DFS (53.7 vs 14.7m, p<0.00001) and OS (61.9 vs 25.7m, p<0.00001) compared to no RT. Likewise, use of adjuvant CT was also associated with improved DFS (54.8 vs 16.5m, p<0.00001) and OS (62.9 vs 26.5m, p<0.00001) compared to no CT. Those who received both chemotherapy and radiotherapy had better outcomes with 5-year DFS (58.3%) and OS (65.2%), compared with those who received monotherapy. On multivariate analysis, grade 3 disease, deep myometrial invasion >50%, and no adjuvant RT or CT were identified as adversely impacting DFS and OS. Conclusions: In stage III endometrial cancer patients, use of both chemotherapy and radiation therapy was associated with improved DFS and OS and therefore should be recommended in all eligible patients after resection.